Implementasi Terapi Gestalt dalam Cerpen Di Sebuah Cafe Karya AD Donggo - Kurniawan, Eva Dwi; Susilo Ayuningtyas, Dwi; Agustiningrum, Vera (Jurnal Penelitian Multidisiplin, 2023)
This research will reveal the implementation of gestalt therapy found in literary works. The literary work that will be used as a source of research is a short story entitled Di A Kafe by AA Danggo. The problem presented is how behavior can be formed from past presence according to Gestalt theory contained in the short story Di Kafe by AA Danggo. This study used a literary psychology approach. The method used is to analyze short story texts that have relevance to gestalt therapy. The results obtained show that gestalt therapy in the aspect of unfinished business is able to reveal the main character's grudge by talking directly to the second character. The main character feels victorious because he has managed to mock and accept his past.